The influence of Corporate Governance Mechanism Towards Company Performance - Musfialdy Musfialdy; Edison Edison; Artis Artis (Indonesian Journal of Economics, Social, and Humanities, 2019)
Corporate Governance explains the relation between many participants in the company that determines the direction of company performance. The purpose of this study is to analyze whether the mechanism of Corporate Governance affects company performance. the results of the study, it can be concluded that institutional ownership, managerial ownership, and audit committees do not have a significant effect on company performance. Independent commissioners have a significant effect on Company Performance.